A robust and reliable methodology to perform GECI-based multi-time point neuronal calcium imaging within mixed cultures of human iPSC-derived cortical neurons - Patel, Niraj; Ouellet, Vincent; Paquet-Mercier, François; Chetoui, Nizar; Bélanger, Erik; Paquet, Marie-Eve; Godin, Antoine G.; Marquet, Pierre (Frontiers in Neuroscience, 2023)
The human induced pluripotent stem cells (iPSCs), with their ability to generate human neural cells (astrocytes and neurons) from patients, hold great promise for understanding the pathophysiology of major neuropsychiatric diseases. Indeed, the in vitro neurodifferentiation of iPSCs, while recapitulating certain major stages of the neurodevelopment in vivo, makes it possible to obtain networks of living human neurons. The culture model presented is particularly attractive within this framework, since it involves iPSCs-derived neuronal cells which more specifically differentiated into cortical neurons. However, these in vitro neuronal networks, which may be heterogeneous in their degree of differentiation, remain challenging to bring to an appropriate level of maturation. It is therefore necessary to develop tools capable of analyzing a large number of cells to assess this maturation process. Calcium (Ca2+) imaging, which has been extensively developed, undoubtedly offers an incredibly good approach, particularly in its versions using genetically encoded calcium indicators (GECI). However, in the context of these iPSCs-derived neural cell cultures, there is a lack of studies which propose Ca2+ imaging methods that can finely characterize the evolution of neuronal maturation during neurodifferentiation process. In this paper, we propose a robust and reliable method for specifically measuring neuronal activity at two different time points of neurodifferentiation process in such human neural cultures. We have developed a specific Ca2+ signal analysis procedure and tested a series of different AAV serotypes to obtain expression levels of GCaMP6f under control of the neuron-specific synapsin1 promoter. The retro serotype has been found to be the most efficient to drive the expression of the GCaMP6f, compatible with long-term neuronal Ca2+ imaging in our human iPSCs-derived neural cultures. An AAV2/retro carrying GCaMP6f under the human Synapsin1 promoter (AAV2/retro-hSyn-GCaMP6f) is an efficient vector that we have identified. To establish the method, Ca2+ measurements were carried out with both hSyn and CAG promoters, the latter being known to provide high transient gene expression across various cell types. Our results stress that this methodology involving AAV2/retro-hSyn-GCaMP6f is suitable for specifically measuring neuronal calcium activities over prolonged periods of time, compatible with the neurodifferentiation process in our mixed human neural cultures.